Considerations for the development of agility during childhood and adolescence - Lloyd, R. S.; Read, P.; Oliver, J. L.; Meyers, R. W.; Nimphius, S.; Jeffreys, I. (Strength and Conditioning Journal, 2013)
Despite being recognized as an essential component of sports performance, agility development in youths is largely under-researched. This article reviews the evidence examining the effects of growth, maturation and training on both change of direction speed and cognitive processing in children and adolescents, and how combined, these factors may influence agility. Training guidelines are provided to help strength and conditioning coaches prescribe agility training for youths at different stages of maturation, in a safe and effective manner.